Organizational Citizenship Behavior dalam Perspektif Maqashid Syariah - Feddy Fabachrain (Green Publisher Indonesia, 2026)
Several previous studies have examined the relationship between Organizational Citizenship Behavior (OCB) and positive workplace behaviors, including Islamic work ethic and work–life balance. However, research that specifically discusses the principles, theories, and characteristics of OCB from the perspective of Maqashid Syariah remains scarce. In fact, Maqashid Syariah can serve as a methodology to assess the usefulness (maslahah) of OCB within organizations. This study aims to enrich the understanding of OCB from the perspective of Maqashid Syariah, so that its implementation in organizations is not only materially oriented but also spiritually grounded. This research uses a descriptive qualitative method with a literature study approach. Data were collected from secondary sources, including academic books and journals. The findings reveal that the five dimensions of OCB have relevance to the five core components of Maqashid Syariah. First, the dimension of altruism corresponds to the protection of religion (hifzu ad-din). Second, conscientiousness relates to the protection of life (hifzu an-nafs). Third, sportsmanship aligns with the protection of intellect (hifzu al-‘aql). Fourth, courtesy corresponds to the protection of property (hifzu al-mal). Fifth, civic virtue relates to the protection of posterity (hifzu an-nasl). This study concludes that integrating Maqashid Syariah into the understanding of OCB offers a more holistic perspective that balances material and spiritual values in organizational behavior.